Analisa Pengaruh Struktur Modal,Ukuran Perusahaan, Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Adhani, Ida; Amelia, Risma (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
The purpose of this study is to determine the effect of Capital Structure, Company Size, and Dividend Policy on Company Value in manufacturing companies in the food and beverages sub-sector listed on the Indonesia Stock Exchange for the 2019-2022 period. This type of data is secondary data from the financial statements of food and beverages companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The number of samples is 11 companies from 30 companies. Sampling is carried out by purposive sampling. The analysis techniques used are Classical Assumption Test, Descriptive Statistics, Multiple Linear Regression, Coefficient of Determination (R2), t Test (Partial Test) and F Test (Simultaneous Test). The results of this study show that the Capital Structure partially has a positive and significant influence on the Company's Value, namely with a t-count value of 4.893 > t-table 2.01954 with a sig value. 0.000 < 0.05, Company Size partially has a negative and significant influence on Company Value, namely with a t-count value of -5.446 < t-table 2.01954 with a value of sig. 0.000 < 0.05, and the Dividend Policy partially does not have a significant effect on Company Value with a t-count value of 1.500 > t-table 2.01954 with a value of sig. 0.142 < 0.05. The results are simultaneously known as Capital Structure, Company Size and Dividend Policy have a significant effect on Company Value, namely with an f-count value of 48,095 > f-table 2,839 with a sig value. 0.000 < 0.05. The predictive ability of the three independent variables to Company Value is seen from the Adjust R Square value of 76.7% while the remaining 23.3% is influenced by other variables outside the research variable.